2004
DOI: 10.1291/hypres.27.79
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Response to Erythropoietin Injection in Hemodialysis and Predialysis Patients

Abstract: lin-1 (ET-1) (7). However, it is not well established whether rHuEPO increases blood pressure via ET-1 in patients on hemodialysis.Patients with chronic renal failure (CRF) and renal anemia are also treated with rHuEPO before the initiation of hemodialysis. In chronic renal failure patients, blood pressure often increases with the progression of renal failure via salt retention. Even though it has been reported that about 20% of predialysis CRF patients show an increase in blood pressure with rHuEPO therapy (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 18 publications
3
31
0
Order By: Relevance
“…An updated mortality curve for cardiovascular disease and infection in 127 Italian CHD patients subdivided according to the presence or not of the C282Y and H63D HFE mutations is shown in figure 1. It is worthy of note that, in patients negative for HFE mutations, we observed a higher mortality due to sepsis, previously associated with a higher iron dosage (Jean, Charra et al 2002;Teehan, Bahdouch et al 2004), and due to cardiovascular disease, possibly linked to hypertension and thromboembolic events related to ESAs (Miyashita, Tojo et al 2004;Phrommintikul, Haas et al 2007) and oxidative stress related to iron (Valenti, Valenti et al 2007). Fig.…”
Section: Hfe Mutations and Survivalmentioning
confidence: 52%
See 1 more Smart Citation
“…An updated mortality curve for cardiovascular disease and infection in 127 Italian CHD patients subdivided according to the presence or not of the C282Y and H63D HFE mutations is shown in figure 1. It is worthy of note that, in patients negative for HFE mutations, we observed a higher mortality due to sepsis, previously associated with a higher iron dosage (Jean, Charra et al 2002;Teehan, Bahdouch et al 2004), and due to cardiovascular disease, possibly linked to hypertension and thromboembolic events related to ESAs (Miyashita, Tojo et al 2004;Phrommintikul, Haas et al 2007) and oxidative stress related to iron (Valenti, Valenti et al 2007). Fig.…”
Section: Hfe Mutations and Survivalmentioning
confidence: 52%
“…As mentioned above, although treatment with ESAs and IV iron formulations (Locatelli, Aljama et al 2004) are generally prescribed, functional iron deficiency is a common finding, determining the need for high doses of ESAs and iron, both associated with adverse events. Indeed, high ESAs doses have been associated with mortality due to cardiovascular events related to hypertension and hypercoagulability (Miyashita, Tojo et al 2004;Phrommintikul, Haas et al 2007;Strippoli, Tognoni et al 2007), whereas excess iron promotes vascular damage by inducing oxidative stress, and heightens the risk of infections (Seifert, von Herrath et al 1987;Jean, Charra et al 2002;Teehan, Bahdouch et al 2004;Kalantar-Zadeh, Regidor et al 2005;Valenti, Valenti et al 2007). The mechanism proposed to explain refractoriness to IV iron was previously related to the inhibition of erythropoiesis and iron recycling from macrophages by inflammation (Stenvinkel 2003).…”
Section: Role Of Hepcidin In Anemia Of Esrdmentioning
confidence: 99%
“…129,130 Although no such increases have been clearly noted in any of the patients in our studies, blood pressure monitoring is absolutely essential and increases in blood pressure with EPO treatment have to be either pharmacologically controlled or should be considered as an exclusion criterion.…”
Section: Blood Pressurementioning
confidence: 70%
“…Strikingly, despite the relatively low number of patients included, the presence of HFE mutations was associated with a 40% reduced hazards ratio of death. It is also worthy of note that, in patients negative for HFE mutations, we observed a higher mortality due to sepsis, previously associated with a higher iron dosage [23,24,25], and due to cardiovascular disease, possibly linked to hypertension and thromboembolic events related to r-HuEPO [10, 20] and oxidative stress related to iron [14]. However, since the study was performed on prevalent patients characterized by a high dialysis vintage, survival bias may have played a role in determining these results.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperferritinemia-associated morbidity is partially explained by non-iron-related factors, as serum ferritin may reflect cytokine release and the malnutrition inflammation cachexia syndrome [4], but even after adjustment for confounding variables, intravenous iron dosage was still associated with increased total and cardiovascular mortality [3, 5]. It has been suggested that iron overload may increase cardiovascular risk by affecting LDL oxidation and endothelial dysfunction [6,7,8], and the administration of intravenous iron has been associated with increased oxidative stress [9], whereas r-HuEPO has been associated with hypertension and embolic events [10]. …”
Section: Introductionmentioning
confidence: 99%